Satisfaction of Graduating Students during Exit Interviews in University of Cebu, Philippines - Etcuban, Jonathan O.; Jereza, Jobie Ruth; Bulanon, Mae Karen; Montecillo, Leah; Olvido, Ivy; Melicor, Sheena Spica (JPAIR Institutional Research, 2016)
The University Guidance Center conducts exit interviews of graduating students as means of assessment for the University’s services, where the graduating students have one final self-assessment before they leave the portals of the university which is considered their home for almost four years. The study aimed to determine the overall student feedback on their learning experiences, importance, and relevance of the skills gained and student satisfaction rating of Student Personnel Services for the school year 2013-2014 and to identify the areas of strengths, and recommend measures for improvement. The study employed descriptive survey method using researcher made questionnaires. The respondents were the 713 graduating students from the different colleges of the University of Cebu Main Campus, Philippines, first semester of the school year 2013-2014. They were advised to answer the four-part questionnaire. The gathered data were treated using frequency, simple percentage, and rank. Findings revealed that majority of the respondents enroll in the course for their parents or relatives encouraged them; the discussion questions contribute to the professional development of the interviewees that affect an in-depth knowledge in their chosen profession. The study concluded that the graduating students are pleased with the services of the Student Personnel Department. However, some suggestions and comments need to be addressed for the improvement of the University in general.